Coordinating a Large, Amalgamated REU Program with Multiple Funding Sources. Issue 3 (16th March 2017) - Fiorini, Eugene; Myers, Kellen; Naqvi, Yusra
Abstract: In this paper, we discuss the challenges of organizing a large REU program amalgamated from multiple funding sources, including diverse participants, mentors, and research projects. We detail the program's structure, activities, and recruitment, and we hope to demonstrate that the organization of this REU is not only beneficial to its participants, but that these ideas can be adapted to the benefit of participants at other REU sites, regardless of the size or structure of the site.